Optimizing Nickel Mine Slope Designs: Integrating Geotechnical Data and Limit Equilibrium Methods - Minmahddun, Anafi; Tugo, Laode Jonas (Program Studi Sarjana Teknik Sipil Universitas Internasional Batam, 2025)
Slope stability in nickel laterite mines is critically influenced by the distinct geotechnical properties of limonite and saprolite weathering profiles. These materials, prevalent in tropical mining regions, exhibit significantly different responses to hydrological and mechanical stresses, necessitating detailed stability assessments for safe mine operations. This study combines field investigations, laboratory testing, and Limit Equilibrium Method (LEM) analysis to evaluate slope stability. Geotechnical parameters were determined through standardized tests and slope stability analyses examined both single-slope (40°-60° angles) and overall-slope configurations with varying bench geometries (widths 3-5m, angles 29°-60°). The analysis demonstrated: (1) Safety factors (SF) decreased 25-30% as slope angles increased from 40° to 60°, with limonite (SF=2.8-2.1) consistently outperforming saprolite (SF=2.4-1.9); (2) Bench width significantly influenced stability, with 5m widths improving SF by 15-20% compared to 3m widths; (3) Optimal stability (SF=1.85) was achieved with gentler geometries (29° slope, 40° bench, 5m width), while steeper configurations approached critical conditions (SF=1.22). The study provides critical insights for designing stable slopes in nickel laterite mines, emphasizing: (1) material-specific slope angles, (2) wider bench designs, and (3) integrated geotechnical-LEM approaches. These findings directly address operational challenges in tropical mining environments, offering practical solutions to enhance safety while maintaining productivity. The methodology establishes a replicable framework for slope stability assessment in weathered geological profiles.